2014
DOI: 10.3109/10715762.2014.886327
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase and its products in synovial fluid of patients with treated or untreated rheumatoid arthritis

Abstract: MPO level is related to IL-8 and IL-18 levels in untreated RA patients. A link has been shown between treatment and decrease of IL-8, MPO specific activity and Hcit in SF. The causal role of MPO in SF inflammation and how treatment can affect MPO specific activity need further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Carbamylation is a chemical reaction mediated by cyanate that modifies lysine residues [5]. Normally the level of cyanate is in equilibrium with urea but specific conditions like inflammation can warp this equilibrium through a myeloperoxidase-dependent mechanism [8, 9]. This leads to the local increase of cyanate levels, thus empowering the degree of carbamylation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Carbamylation is a chemical reaction mediated by cyanate that modifies lysine residues [5]. Normally the level of cyanate is in equilibrium with urea but specific conditions like inflammation can warp this equilibrium through a myeloperoxidase-dependent mechanism [8, 9]. This leads to the local increase of cyanate levels, thus empowering the degree of carbamylation [10].…”
Section: Introductionmentioning
confidence: 99%
“…When the rate of oxidants production surpasses the capability of antioxidant systems to eliminate these oxidants products, oxidative stress ensues, which leads to subsequent injury to cells and tissues . Previous clinical studies have shown increased prooxidant and oxidative activities, along with decreased antioxidant defence activities in patients with RA …”
Section: Introductionmentioning
confidence: 95%
“…However, there was inconsistency as to the correlation between MPO levels in the plasma and disease activity score, as one study showed correlation, while another did not [83,84]. Additionally, RA patients exhibited higher levels of MPO and its product Cl-Tyr in synovial fluids compared to osteoarthritis (OA) patients [85]. RA patients treated with disease-modifying antirheumatic drugs and/or biological agents exhibited decreased MPO-specific activity in the joints [85].…”
Section: Mpo and Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…Additionally, RA patients exhibited higher levels of MPO and its product Cl-Tyr in synovial fluids compared to osteoarthritis (OA) patients [85]. RA patients treated with disease-modifying antirheumatic drugs and/or biological agents exhibited decreased MPO-specific activity in the joints [85]. These data correlate well with murine studies, where injection of active or inactive MPO into the joints exacerbated disease, while decreased MPO levels in affected joints, observed after treatment with atrovastatin or blockade of CXCR1/CXCR2 receptors, correlated with decreased severity disease [8688].…”
Section: Mpo and Rheumatoid Arthritis (Ra)mentioning
confidence: 99%